Protecting Electricity Retailers Against Price Volatility : The Electricity Tariff Equalization Fund in New South Wales - Kerf, Michel; Groom, Eric (World Bank, Washington, DC, 2012)
Most commentators agree that the benefits of competitive electricity markets will materialize only if wholesale prices are allowed to fluctuate more or less freely so as to provide adequate pricing signals to generators. Most also agree, however, that small electricity users need to be protected against wholesale price volatility through stable, predictable retail rates. That raises a difficult question about whether the retailers or distributors, caught in the middle, also need some protection, especially early in the development of competitive markets. The Australian state of New South Wales has used a transitional mechanism to provide such protection. Lessons learned from this experience can be of interest for other countries.